Tetracyclines disturb mitochondrial function across eukaryotic models: a call for caution in biomedical research - Moullan, Norman (Cell Rep, 2015)
In recent years, tetracyclines, such as doxycycline, have become broadly used to control gene expression by virtue of the Tet-On/Tet-Off systems. The wide range of direct effects of tetracycline use has, however, not been fully appreciated. We show here that these antibiotics induce a mitonuclear protein imbalance through their effects on mitochondrial translation, an effect that likely reflects the evolutionary relationship between mitochondria and proteobacteria. Tetracyclines, Even at low concentrations, tetracyclines induce mitochondrial proteotoxic stress, leading to changes in nuclear gene expression and altered mitochondrial dynamics and function in commonly used cell types, as well as worms, flies, mice, and plants. Since tetracyclines are so widely applied in research, scientists should be aware of their potentially confounding effects on experimental results. Furthermore, these results caution against extensive use of tetracyclines in livestock due to potential downstream impacts on the environment and human health.